Understanding the experiences of recruitment from African American males within master's level counseling programs: A narrative inquiry - Johnson, Marlon (2019)
Counselor educators who work at predominantly White institutions recognize the need to develop recruitment and retention strategies for African American men. Yet, there is a lack of research regarding the experiences and processes through which African American men choose a counselor training program. The purpose of this narrative inquiry was to explore the narratives of recruitment from African American men who enter CACREP-accredited, master’s-level counselor training programs. This study addressed two research questions: What are the recruitment experiences of African American men enrolled in predominantly White, master’s-level, CACREP-accredited counseling programs? and What influences an African American man’s decisions to enroll in predominantly White, master’s-level, CACREP-accredited programs? Narrative inquiry (Squire, 2013) was used to analyze goal statements, semi-structured interviews, and reflective letters with four African American men within the first 30 months of their master’s counseling program. Four major themes were constructed: relationships communicate importance, collaboration fosters motion, messages influence direction, and recruitment requires belonging. The findings highlighted the importance of building relationships with African American communities to diminish the gendered and racialized myths surrounding mental health care and counseling careers.Recommendations for future research and implications for counselor educators, mental health counselors, and school counselors were provided